Responding to the Spiritual Needs of Palliative Care Patients: A Randomized Controlled Trial to Test the Effectiveness of the Kibo Therapeutic Interview - Soto-Rubio, Ana; Perez-Marin, Marian; Rudilla, David; Galiana, Laura; Oliver, Amparo; Fombuena, Miguel; Barreto, Pilar (Frontiers in Psychology, 2020)
Context The WHO recognizes the need to attend to patients' spiritual needs as being fundamental to comprehensive and high-quality end-of-life care. Spiritual needs must be attended since the resolution of biological and psychosocial issues is insufficient to reduce patients' suffering. Associations have been found between spiritual needs and other variables of importance for patients in palliative care. Despite the consensus that exists regarding the importance of assessing and attending to spiritual needs, professionals encounter many difficulties in attempting to do so. Objectives Our study aims to demonstrate the benefits that the KIBO therapeutic interview in palliative care patients can have for spirituality, demoralization, and resilience. Methods A parallel randomized controlled trial of two groups was undertaken. Information on 60 palliative care patients during pre and post-intervention time points was gathered. Results ANOVAs pointed out a statistically significant effect of the intervention on the dimension of transpersonal spirituality. The ANCOVA studying the effect of the intervention on resilience also pointed to its effectiveness. When the means of demoralization were examined, a higher decrease in the levels of the demoralization for patients in the intervention group was observed, when compared to patients in the control group. Conclusion Our findings point at this interview as an effective to attend to the spiritual needs of palliative patients, reducing demoralization, and increasing resilience. Future research could focus on a broader sample, and on the effects of this interview on the family caregivers, mourners, and health care professionals. ClinicalTrials.gov registration number: NCT03995095, URL: https://clinicaltrials.gov/ct2/show/NCT03995095